Electrochemically reduced Ti0_2 nanowires decorated with carbon quantum dots for enhanced photocatalytic water splitting (2021)
TiO_2 nanowires are frequently used in photoelectrochemical water splitting for their extended area, chemical stability, and adequate band positioning. Yet, limited charge mobility and short electronic carrier lifetimes are recognized as limiting aspects of the material. Herein we present 3 different strategies to overcome these short comings, firstly a morphological and impedance study is conducted to determine the effect of nanowire growth over TiO_2 nanoparticle seeded fluorine tin oxide substrates and post-annealing synthesis. Afterwards, we present a new simple electrochemical reduction procedure for the synthesis of reduced TiO_2 nanowires with enhanced charge transfer capabilities due to the induction of Ti^(+3) defects that serve as hole traps and oxygen vacancies..